Francisella tularensis Bacteremia: A Case Report from Sudan - Salma E. R. Mohamed; Aymun I. Mubarak; Lamia O. Alfarooq (Case Reports in Infectious Diseases)
Francisella tularensis is a highly virulent intracellular gram-negative bacterium. The organism is usually isolated from wild and domestic animals and invertebrate. Man gets infection by direct contact with those animals or their products but the most common mode of transmission is via arthropod vectors. The disease is endemic in North America, parts of Europe, and Asia but has never been reported in Africa. A 29-year old male living in a rural area of Southern Sudan has been maintained on continuous ambulatory peritoneal dialysis for two years. He presented to our center in May 2010 complaining of fever, dry cough, shortness of breath, and abdominal discomfort for four days. He was very ill, pale, and dehydrated. There were enlarged tender submandibular lymph nodes, but no mouth ulcers or other palpable lymph nodes. Peritonitis was excluded by effluent white blood cell count and culture. Empiric antibiotic treatment with ceftriaxon, and ciprofloxacin was started. Gram-negative coccobacilli were isolated by blood culture. The organism was identified as Francisella tularensis. We started him on a ten-day course of gentamicin after which he improved. This is, to the best of our knowledge, the first reported case of bacteremia caused by Francisella tularensis in Sudan.